If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3 = 7x + -1x Reorder the terms: -3 + 7x = 7x + -1x Combine like terms: 7x + -1x = 6x -3 + 7x = 6x Solving -3 + 7x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3 + 7x + -6x = 6x + -6x Combine like terms: 7x + -6x = 1x -3 + 1x = 6x + -6x Combine like terms: 6x + -6x = 0 -3 + 1x = 0 Add '3' to each side of the equation. -3 + 3 + 1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 0 + 3 1x = 0 + 3 Combine like terms: 0 + 3 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 272-3x=42x+17 | | 1.78g-6=0.23 | | -4x+6(2x-7)=-31-2x | | 4x+50=x+10 | | g(x)=-5x+2 | | 128+1x=24 | | x*2+x-5=45 | | 2x+40=y | | 10y-7y-11=21.22 | | 13y-8y-4=47.60 | | 3x-8=x+5 | | -2(3b+3)=3b+39 | | 17x=19x | | 14y-12y=6 | | 3x-4=11x-27 | | 15y-11y=12 | | x+27=4 | | 3x+13x=80 | | 2x+4y=-23 | | 13x-6=11x+14 | | 12y-10y=8 | | 5x+17=15x+3 | | y+15-8=12 | | 27x-5=26x | | 4x+8+1=9 | | 12m+46=1138.00 | | 50x-2=49x | | -2(x+5)-2=-8+4 | | 6z+4z=9z-4 | | X-16=16+2x | | 7x+5=8x-5 | | 34+6=63 |